Macrophages of the "heart-kidney" axis: their dynamics and correlations with clinical data and outcomes in patients with myocardial infarction - Kercheva, Maria; Ryabov, Vyacheslav; Gombozhapova, Aleksandra; Rebenkova, Maria; Kzhyshkowska, Julia (Journal of Personalized Medicine, 2022)
Changes in the macrophage infiltration of kidneys in rodents under ischemic conditions may affect cardiac macrophages and lead to development of adaptive cardiac remodeling. The aim of our study was to translate experimental findings into clinically relevant applications and assess the features of macrophage infiltration of the kidney and its correlations with changes in macrophage infiltration of the myocardium and with clinical data in patients who experienced a fatal myocardial infarction (MI). We examined fragments of both organs taken from patients (n = 30) who suffered from fatal MI. Macrophage infiltration was assessed by immunohistochemistry. Macrophage infiltration of the kidneys in patients with fatal MI is heterogeneous. The early period of MI was shown to be characterized by the prevalence of CD163+ and CD68+ cells, and in the long-term period by only CD163+ cells. However, only the level of CD206+ cells in the kidneys showed the dynamics representing the late MI period. Its decrease accompanied increase in the numbers of cardiac CD68+, CD163+, CD206+, and stabilin-1+ cells in the infarct area. Kidney CD206+ cells had more correlations with cardiac macrophages than other cells, and the presence of these cells also correlated with impairment of renal function and early death.
Gesehen am 23.11.2023